Kemampuan Pemecahan Masalah Siswa Dalam Menyelesaikan Soal Matematika Terintegrasi Islam - Asna, Rani; Imamuddin, M.; Rahmat, Tasnim; Firmanti, Pipit (Ar-Riyadhiyyat: Journal of Mathematics Education, 2024)
Mathematics is very close to Islamic schools, so students are required to understand and master mathematics in order to optimize their devotion to Allah SWT. Learning in Islamic schools should be carried out in an Islamic manner and students should be able to solve mathematical problems. For this reason, Islamic integrated mathematical problem solving questions are needed in learning. This research aims to determine students' mathematics problem solving abilities (KPM) in solving Islamic integrated mathematics problems in class IV.B SDIT Haji Djalaluddin. The type of research used is descriptive research carried out using a quantitative approach. The subjects in this research were all class IV.B students at SDIT Haji Djalaluddin. The data collection used by researchers during research is by using test questions. The instrument used in this research is the Islamic Integrated Mathematics KPM test questions. Based on the KPM test, students in working on integrated Islamic mathematics questions in answering 3 problem solving questions can be seen in the form of a percentage for each question, namely for question number 1 it is 66.80% with good criteria, for question number 2 it is 54% with sufficient criteria. , for question number 3 it is 52.80% with less criteria.